2003
DOI: 10.1055/s-2003-40364
|View full text |Cite
|
Sign up to set email alerts
|

Reduction or elimination of postoperative pain medication after mastectomy through use of a temporarily placed local anaesthetic pump vs. control group

Abstract: Use of an ON-Q pain management pump could significantly reduce or even eliminate postoperative need for opioids analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, the technique tested involved infiltration via wound drains which deposited local anaesthetic in a more superficial tissue plane than the subpectoral plane and did not use a continuous infusion. Non-randomised, non-blinded, retrospective and observational studies of local anaesthetic infusion24–26 suggest more favourable results. Baroody et al 25 demonstrated a fivefold reduction in analgesic requirement following local anaesthetic infusion after reconstructive breast surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the technique tested involved infiltration via wound drains which deposited local anaesthetic in a more superficial tissue plane than the subpectoral plane and did not use a continuous infusion. Non-randomised, non-blinded, retrospective and observational studies of local anaesthetic infusion24–26 suggest more favourable results. Baroody et al 25 demonstrated a fivefold reduction in analgesic requirement following local anaesthetic infusion after reconstructive breast surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Baroody et al 25 demonstrated a fivefold reduction in analgesic requirement following local anaesthetic infusion after reconstructive breast surgery. Morrison et al 24 compared postoperative opioid use in mastectomy patients receiving local anaesthetic infusion or no infusion and found a significant reduction in opiate use and hospital length of stay in the local anaesthetic arm. However, this was an unblinded retrospective analysis and made no attempt to investigate chronic pain or arm mobility.…”
Section: Introductionmentioning
confidence: 99%